2015
DOI: 10.1051/matecconf/20152900005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of material properties for short fibre reinforced C/C-SiC

Abstract: Abstract. Determining the mechanical properties of short fibre reinforced CMC using standard sized coupons has always been a challenge due to a high statistical scattering of the measured values. Although the random orientation of short fibres results in a quasi-isotropic material behavior of 2D-structures with a sufficiently large volume, the small volume typical for test coupons usually results in a non-isotropic fibre orientation in the tested volume. This paper describes a method for manufacturing unidirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…In fact, Ref. [62] demonstrates that compared to the identical material made of randomly orientated chopped fibres, the unidirectional material has a 50% increase in the flexural strength. No visible difference in the pull-out was found between the samples with different amounts of the fibres (20, 35, and 50 vol%).…”
Section: Morphologies Of Fracture Surfacesmentioning
confidence: 99%
“…In fact, Ref. [62] demonstrates that compared to the identical material made of randomly orientated chopped fibres, the unidirectional material has a 50% increase in the flexural strength. No visible difference in the pull-out was found between the samples with different amounts of the fibres (20, 35, and 50 vol%).…”
Section: Morphologies Of Fracture Surfacesmentioning
confidence: 99%
“…No references were found on modeling of the PIP process for CMCs, though experimental studies on this manufacturing process have been reported. Studies on polycarbosilanederived SiC ceramic 25 and SiC/SiC composite 26,27 have shown that porosity decreases and mechanical properties improve with the increasing number of PIP cycles. Zhu et al 28 show that increasing pyrolysis temperature and the concentration of SiC fillers in polycarbosilane polymer result in improved mechanical properties in two-dimensional Carbon/ SiC (C/SiC) composites fabricated using the PIP process.…”
Section: Sic Padsmentioning
confidence: 99%
“…Previous research revealed that distinctly different friction and wear performance were presented in carbon fiber reinforced carbon (C/C) composites with different carbon fiber orientations 26 . Currently, researchers have tried to design fiber orientations of C/C‐SiC composites for further development of mechanical properties and oxidation properties 27–30 . According to Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations